Rare cause of repeated pulmonary embolism: a case of primary pleural squamous cell carcinoma and literature review - Zhongzhong Chen; Tingting Feng; Meng Wang; Xingxiang Xu; Yuxiu Wang; Yiran Li; Lingfeng Min (BMC Pulmonary Medicine, 2020)
Abstract Background Malignant tumors are risk factors for a pulmonary embolism (PE), and a PE caused by a tumor is not uncommon. Primary pleural squamous cell carcinoma (PPSCC) is a rare malignancy; thus, a related PE is extremely rare. Case presentation A previously healthy 49-year-old female patient was admitted to Northern Jiangsu People’s Hospital owing to chest tightness, cough, and breathing difficulty that persisted for 3 days. Following admission, a computed tomography (CT) pulmonary angiography revealed an embolism in the main pulmonary artery, upper and lower pulmonary artery branch. The patient was treated with alteplase, warfarin, and antibiotics. Over the following year, she experienced recurrent chest pain and tightness and breathing difficulty, with multiple CT pulmonary angiography revealing thrombosis in the right and left main pulmonary artery. No abnormalities were observed in surrogate markers of autoimmune diseases, tumor antigen testing, or ultrasonography; thus, the cause of recurrent PE was not identified. Subsequently, a positron emission tomography-computed tomography (PET-CT) examination revealed diffuse heterogeneous thickening of the right pleura and substantially increased glucose metabolism. A CT-guided pleural biopsy was performed, and histopathological examination of the pleura eventually revealed a diagnosis of PPSCC. Conclusions PPSCC is a rare tumor that lacks specific clinical manifestations and is difficult to detect with imaging techniques. The occurrence of PE as the primary manifesting symptom in a patient with PPSCC is extremely rare. Thus, malignant tumors should be considered in patients with no risk factors for PE and/or in those with recurrent PE. An immediate diagnosis and adequate intervention can be achieved with increased awareness of this diagnosis and subsequent related examinations.